The Application of Nanotechnology in Immunotherapy based Combinations for Cancer Treatment - Li, Hongxia; Fu, Qiuxia; Muluh, Tobias A.; Shinge, Shafiu A. Umar; Fu, Shaozhi; Wu, JingBo (Recent Patents on Anti-Cancer Drug Discovery, 2023)
There has been a great amount of advancement in the early field of nano-immunotherapy and combination therapy. Persistent consideration regarding the clinical challenges and therapeutic hindrance should be tended to achieve therapeutic efficacy and potential. In this review, we will address how nanotechnology could defeat the difficulties resulting from cancer immunotherapy, how nanoparticles’ utilization can enhance the efficacy of immune checkpoint blockers, and reconstituting the tumor microenvironment can promote antitumor responses. Moreover, this review discusses how nanoparticles mediate therapeutic modalities like chemotherapy, photodynamic therapy, photothermal therapy, and radiotherapy, which are used to target and destroy cancerous cells, initiate the release of tumor antigens, and can trigger anti-tumor immunity reactions. Furthermore, we analyzed the potential benefits of immunotherapy combinatorial using the nanoparticle delivery system to prevent tumor recurrence, hinder metastases, and decrease systemic toxicity of major organs and healthy cells common with uncontrolled targeting.
Keywords: Immunity